2016
DOI: 10.1108/ijem-05-2014-0065
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability insights from the mission statements of leading Brazilian Universities

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Similarly, lack of internal governance, administrative practices and policies were reported in Malaysia as well as in Saudi's HEIs (Alshuwaikhat et al, 2016;Goni et al, 2017). In contrast, Deus et al (2016) reported a lack of sustainability-focused vision and mission in the top HEIs of Brazil. Moreover, Lozano et al (2015) reported HEIs' commitment to sustainability as a factor in low sustainability practices.…”
Section: Integrating Sustainability Into Operations Of Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, lack of internal governance, administrative practices and policies were reported in Malaysia as well as in Saudi's HEIs (Alshuwaikhat et al, 2016;Goni et al, 2017). In contrast, Deus et al (2016) reported a lack of sustainability-focused vision and mission in the top HEIs of Brazil. Moreover, Lozano et al (2015) reported HEIs' commitment to sustainability as a factor in low sustainability practices.…”
Section: Integrating Sustainability Into Operations Of Higher Education Institutionsmentioning
confidence: 99%
“…All-encompassing, the sustainability in Saudi HEIs are reported yet to be at the initial stage (Alshuwaikhat et al, 2016). Through analytical analysis, Deus et al (2016) identified a lack of strategic alignment in HEI's of Brazil toward sustainability as they did not show sustainable indicators on the mission statements. Although there has been progress on the United Nations Decade of Education for Sustainable Development (UNDESD) initiative, yet sustainability reporting in HEIs is inconclusive (Ceulemans et al, 2015;Yanez et al, 2019).…”
Section: Education For Sustainable Development Reporting From Various Parts Of the Worldmentioning
confidence: 99%
“…More discouragingly, Lopez and Martin (2018) discovered that a mere 19% of a sample of 347 universities from the Sustainability Endowment Institute’s Green Card in Canada and the USA mention sustainability in their website mission statements. In other countries, such as Australia (Lee et al , 2013) or Brazil (Deus et al , 2016), the situation is quite similar.…”
Section: Introductionmentioning
confidence: 98%
“…Hoover and Harder (), note, “There is widespread recognition that higher education institutions have an important role to play in the transition toward a more sustainable global society” (p. 175). According to Deus, Battistelle, and Silva () in their research on mission statements in Brazilian universities, the authors recommend that “Higher education managers should review the universities mission statements in terms of a sustainability overview and improve the statements” (p. 403).…”
Section: Introductionmentioning
confidence: 99%